The effect of aflatoxins B1 (AFB1) on chick embryo - Bahri, Sjamsul; Widiastuti, R; Mustikaningsih, Y (Indonesian Animal Sciences Society, 2005)
Aflatoxins are toxic compounds which occurred in cereals especially low qualities corn and peanuts. Aflatoxins are mutagenic, teratogenic and carcinogenic. The presence of aflatoxin in food including derived food in Indonesia had been observed, however, the observation on its toxicity effect is still limited. This research was conducted to study the effect of innoculation of aflatoxin B1 (AFB1) on the development of embryonic chicken egg, mortality and hatchability. The AFB1 was innoculated 10 Î¼l in each 5 days age embryonic egg through air sacs dosaged 0; 15,6; 31,2; 62,5; 125 and 250 ng. The results showed that hatchability of those embryos were 66, 28, 26, 16, 0 and 0% respectively for 0; 15,6; 31,2; 62,5; 125 and 250 ng innoculation of AFB1. Innoculation of AFB1 caused malformation of the embryos, malabsorbtion of the yolk egg. The weight of hatched eggs was not significantly different in each group, eventhough there was a tendency that high AFB1 innoculation will decreased the live weight. Â Â Key Words: Aflatoxin B1, Toxicity, Chick Embryo